The threshold of the residual pitch in three-component inharmonic stimuli - Adam Mielczarek (Archives of Acoustics)
The paper presents the research results of the first effect of pitch shift in three-component inharmonic complexes. The appearance of this effect is the most important evidence that the difference tone introduced by the nonlinearity of a hearing system does not influence residual pitch perception in three-component complexes. The subjects in the adjustment procedure matched the three-component complexes pitch to the same sensation produced by pure tone. The subjects listened to three components, the harmonics of 200 Hz, which were equally shifted in the frequency domain. A 30 Hz shift was applied. The frequency range was 630–4430. The hearing experiments reveal the existence of the threshold of the appearance of the virtual pitch corresponding near to $F_1 = 200$ Hz. These results are explained using the pitch perception models based on the Licklider duplex theory and Terhardt’s pitch algorithm.